Retinal ganglion cell complex and visual evoked potentials in levetiracetam treatment. (2nd July 2020) - Hazirolan, Dicle; Duman, Melih; Guler, Selda Keskin; Uney, Guner; Ornek, Firdevs
Abstract: Purpose: To examine central macular, RNFL (retinal nerve fibre layer), GCC (ganglion cell complex) thicknesses; and VEPs (visual evoked potential) in epileptic patients using levetiracetam for at least one year. Materials and Methods: Sixteen focal epileptic patients receiving levetiracetam monotherapy and 16 healthy subjects were included in the study. Central macular, RNFL and GCC thicknesses according to spectral domain OCT (optical coherence tomography); and VEPs parameters were compared between patients and healthy subjects. Results: The mean age of patient and control groups were 40 ± 16 and 38 ± 12 years respectively ( p  > 0.05). The patient group was on levetiracetam therapy for 64 ± 45 (12–168) months. Central macular thickness was thinner in the patient group ( p  = 0.008). There was no difference among groups regarding RNFL thicknesses. GCC thicknesses in all quadrants were similar among groups, except the superior quadrant; which was thinner in the patient group ( p  = 0.03). P100 amplitude in 30 min pattern was lower in the patient group ( p  = 0.04). N135 latency in 15 min ( p  = 0.03) and 7 min patterns ( p  = 0.01) was longer in the patient group. Conclusion: Central macular and GCC thicknesses; and VEP parameters in patients receiving levetiracetam treatment may differ from healthy subjects.